2007
DOI: 10.1111/j.1365-3156.2006.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of artemether–lumefantrine given once daily for the treatment of uncomplicated multidrug‐resistant falciparum malaria

Abstract: Artemether-lumefantrine efficacy is reduced by once-daily dosing, because absorption of lumefantrine is dose limited. At currently recommended doses, this antimalarial should be given twice daily in a 3-day regimen, with food containing fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 17 publications
6
74
0
Order By: Relevance
“…Moreover, the rate and extent of lumefantrine absorption assessed in our study (C max , 6.3 and 7.7 g/ml for dispersible and crushed tablets, respectively; AUCs, 574 and 636 g ⅐ h/ ml, respectively) were comparable to those determined in adult malaria patients from Thailand and pediatric and adult patients from Africa (3,7,21). In one study conducted in Ugandan children (26.5-kg body weight, on average), the geometric mean lumefantrine C max was 6.8 g/ml and the AUC from times zero to 120 h after the last dose amounted to 195 g ⅐ h/ml (19).…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the rate and extent of lumefantrine absorption assessed in our study (C max , 6.3 and 7.7 g/ml for dispersible and crushed tablets, respectively; AUCs, 574 and 636 g ⅐ h/ ml, respectively) were comparable to those determined in adult malaria patients from Thailand and pediatric and adult patients from Africa (3,7,21). In one study conducted in Ugandan children (26.5-kg body weight, on average), the geometric mean lumefantrine C max was 6.8 g/ml and the AUC from times zero to 120 h after the last dose amounted to 195 g ⅐ h/ml (19).…”
Section: Discussionsupporting
confidence: 56%
“…The simulations suggested that a 100% dose increase would achieve the target day 7 plasma lumefantrine concentrations in 95% of these women with a normal 3-day regimen. This may not achieve its objective because of the dose-limited absorption of lumefantrine (5). Therefore, we suggest the use of a 5-day instead of a 3-day course of artemether-lumefantrine in later pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…4. No simulations of higher-dose regimens are shown because of the dose-dependent oral absorption of lumefantrine (5,12). The duration of artemether and dihydroartemisinin exposure is assumed to last for approximately 6 h after each dose (i.e., three half-lives).…”
Section: Dose Regimen Simulationsmentioning
confidence: 99%
“…Various therapeutic thresholds have been reported for the day 7 lumefantrine concentration, ranging between 175 and 500 ng/ml, depending on the prevalence of resistance and the method used for determining this threshold; of these, 280 ng/ml is the most widely cited (3,12,13,23,27,28,41). Patients with uncomplicated malaria with day 7 lumefantrine concentrations below these concentrations are potentially at increased risk of treatment failure (3,12,13,23,27,28,41). Therapeutic pharmacokinetic thresholds have yet to be defined for the artemisinin derivatives.…”
mentioning
confidence: 99%